2021
DOI: 10.5114/aoms/115011
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific differences in plasma ferritin in adolescents smoking cigarettes versus waterpipe smoking: the Irbid-TRY Project

Abstract: IntroductionFerritin has been implicated in body physiology and pathology. Smoking cigarettes (Cg) alters ferritin metabolism. Waterpipe (Wp) smoking has recently reemerged as a global epidemic and is linked to the most devas�tating diseases. However, the effect of smoking Wp on ferritin is not known. Therefore, the current study compared plasma ferritin in adolescents smok�ing Cg, Wp, both (CgWp) versus never smoked.Material and methodsSelf-reported smoking status and plasma ferritin lev�els were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…One study found high serum ferritin levels in adolescent boys (n = 470) and girls (n = 379) with different types of smoking, compared to their non-smoker counterparts. In addition, they detected lower serum ferritin values among female smokers, compared to male smokers (104). The sex difference in serum ferritin reported in nicotine users could be explained in the light of the findings presented by Benowitz et al They reported higher clearance and faster metabolism of nicotine in pre-menopausal women compared to men, particularly women on combined and estrogen-only contraceptives, implying a role for sex hormones in nicotine metabolism (105).…”
Section: Discussionmentioning
confidence: 87%
“…One study found high serum ferritin levels in adolescent boys (n = 470) and girls (n = 379) with different types of smoking, compared to their non-smoker counterparts. In addition, they detected lower serum ferritin values among female smokers, compared to male smokers (104). The sex difference in serum ferritin reported in nicotine users could be explained in the light of the findings presented by Benowitz et al They reported higher clearance and faster metabolism of nicotine in pre-menopausal women compared to men, particularly women on combined and estrogen-only contraceptives, implying a role for sex hormones in nicotine metabolism (105).…”
Section: Discussionmentioning
confidence: 87%
“…With informed consent, their peripheral blood was collected in the third trimester (gestational week: 34.6 ±4.0) and after delivery using EDTA anticoagulant tubes. Then, the blood samples were centrifuged twice at 3000 rpm at 4°C to obtain plasma and stored at –80°C until testing [ 5 ]. Based on the pregnancy outcome, we finally selected samples from seven pregnant women carrying male fetuses for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Freely floating iron can cause toxic effects, so ferritin synthesis is induced to store iron safely. 6 Cigarette smoking has been associated with alterations in iron balance, not only in the lungs but also in other parts of the body. Specifically, there have been reports of increased iron levels in alveolar macrophages and bronchoalveolar lavage fluid.…”
Section: Introductionmentioning
confidence: 99%